Improving TRIGA PUSPATI Reactor performance with a PI controller and PSO-optimized fractional order lead-lag compensator - Che Soh, Azura; Mohd Noor, Samsul Bahari; Abdul Rahman, Ribhan Zafira; Abdullah, Nor Arymaswati; Abdul Karim, Julia (Universiti Malaysia Sabah, 2024)
Controlling the power level in the TRIGA PUSPATI Reactor (RTP) is crucial for both producing accurate power output and managing reactor activity and power distribution. Currently, the RTP uses a Feedback Controller Algorithm (FCA) based on a Proportional-Integral (PI) controller to improve steady-state error during operation. However, this existing model faces issues such as delays in reaching a steady state and an inability to minimize errors due to insufficient power accuracy and an ineffective controller. To address these issues, a new structure called the Fractional Order Lead-Lag Compensator (FOLLC) has been introduced. Traditionally, the FOLLC structure is identified through loop shaping using Bode plots and root locus in the frequency response domain. In this study, however, the Particle Swarm Optimization (PSO) technique has been employed to estimate the values of the compensator’s poles and zeros. Integrating the compensator with the PSO approach improved the reactor core system's ability to reach and maintain the desired power output while minimizing deviations from the target power level, achieving Residual Mean Percentage (RMP) values between 0.75% and 2.35%. In comparison, the model without a compensator had much higher RMP values of 3.45% to 27.48%, showing a less accurate match with the real plant. This integration enhanced the overall performance of the reactor core system.